2002
DOI: 10.1128/jb.184.11.3034-3043.2002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mycobacteriophage Ms6 Lysis Genes Is Driven by Two σ70-Like Promoters and Is Dependent on a Transcription Termination Signal Present in the Leader RNA

Abstract: A mycobacteriophage Ms6 strong promoter region (P lys ) was isolated by using transcriptional fusions with the lacZ reporter gene. Two tandem 70 -like promoter sequences (P1 and P2) were found in this region. DNA sequencing of the promoter downstream region revealed a 214-bp leader sequence followed by five adjacent coding regions of 231 bp (ORF1), 1,152 bp (ORF2), 996 bp (ORF3), 231 bp (ORF4), and 372 (ORF5). ORF1 has the potential to encode a 77-amino-acid protein which revealed similarity to mycobacteriopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 30 publications
1
63
0
Order By: Relevance
“…The gene lysB, which is localized downstream of the endolysin gene lysA, and immediately upstream of the holin gene hol, is 996 bp in length, and encodes a 332 aa protein (Garcia et al, 2002). The presence of the pentapeptide Gly-Tyr-Ser-Gln-Gly within the amino acid sequence matches the consensus motif Gly-X-Ser-X-Gly characteristic of lipolytic enzymes, and led us to search for lipolytic activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gene lysB, which is localized downstream of the endolysin gene lysA, and immediately upstream of the holin gene hol, is 996 bp in length, and encodes a 332 aa protein (Garcia et al, 2002). The presence of the pentapeptide Gly-Tyr-Ser-Gln-Gly within the amino acid sequence matches the consensus motif Gly-X-Ser-X-Gly characteristic of lipolytic enzymes, and led us to search for lipolytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Growth and viability of the recombinant strain E. coli JM109 (pMP302) was not affected, even after the addition of 2 % CHCl 3 (data not shown). It has been shown for other phages that expression of a bacteriophage lysin gene in E. coli causes cellular lysis after permeabilization of the plasma membrane with chloroform (Chandry et al, 1997;Henrich et al, 1995); this effect is also observed with the lysin LysA of mycobacteriophage Ms6 (Garcia et al, 2002). The result indicates that LysB is not an additional endolysin.…”
Section: Cloning and Expression Of The Lysb Genementioning
confidence: 94%
See 1 more Smart Citation
“…Earlier studies with lysins have utilized chloroform to make the plasma membrane permeable that then allows the diffusion of lysins to the cell wall peptidoglycan and its digestion (53)(54)(55). Several other studies have followed the lysin effect after its co-expression with Holin (25,56).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in order to identify the promoter for the endolysin gene of mycobacteriophage Ms6, the desired region was fused to the lacZ reporter. It was then demonstrated that lacZ was expressed from two s 70 -like promoters, providing evidence that transcription of endolysin genes can be carried out by host transcription factors (Garcia et al, 2002). It would be of immense interest to explore the involvement of various transcription factors in the expression of endolysin genes.…”
Section: Introductionmentioning
confidence: 99%